Unified Perspectives in Urban Transport Sustainability: An AHP-Based Comparative Analysis of National and Local Indicator Weights (European Journal of Engineering Science and Technology, 2024)
This study investigates the differences in urban transport sustainability indicators from national and local perspectives using Amman, Jordan as a case study. Employing the Analytic Hierarchy Process (AHP) method, we aim to understand the weighted importance of various sustainability indicators as viewed by experts at different administrative levels. A structured survey was conducted with 30 national and 30 local experts gathering their insights through pairwise comparisons of indicators. The results reveal significant disparities between national and local priorities, highlighting the need for integrated approaches in urban transport planning. National experts prioritize public transport coverage and air quality, reflecting broader strategic goals, while local experts emphasize pedestrian infrastructure and accessibility to green spaces, focusing on community-specific needs. This comparative analysis underscores the importance of balancing both perspectives to enhance urban transport sustainability effectively. The findings suggest that integrating national and local views can lead to more comprehensive and inclusive transport policies. This research contributes to the existing literature by addressing the often-overlooked social dimension of sustainability and providing a practical framework for evaluating and balancing national and local priorities in urban transport planning.